Epidemiological analysis of yam mosaic virus (YMV) infection risk factors and its implications for clean seed yam systems - Osundahunsi, B.; Oviasuyi, T.; Odu, B.O.; Aighewi, B.; Kumar, P. Lava (2022)
Yam mosaic virus (YMV) is a major threat to yam production in West Africa. This study determined factors contributing to the spread of YMV in yam fields, including the role of aphid vectors, seed-borne infections, YMV inoculum in the fields, weather, genetic diversity of the virus, and spatial distance between infected sources. The findings of this study are useful for refining YMV control measures, developing a model for disease risk assessment under different scenarios, and guiding clean seed yam production systems.